Antioxidant and Tyrosinase Inhibitory Activities of the extracts from Leaves of Suaeda maritime L. - Wattana, Wanna; Poungraya, Kridsana; Sudta, Pichit (Srinagarind Medical Journal, 2022)
Background and Objective: Seablite (Suaeda maritime (L.) Dumort.) is a plant belonging in Chenopodiaceae. Seablite is a domestic plant in various regions of Thailand. This research aimed to study the antioxidant and tyrosinase inhibitory activities of the ethanolic extracts from both fresh and dried leaves of Suaeda maritime (L.) Dumort. Methods: This study was experimental research. In this research seablite was extracted from fresh leaves and dry leaves. The antioxidant activity was evaluated using DPPH free radical scavenging method and the tyrosinase inhibitory activity was performed by the modified dopachrome method. Results: The results indicated that ethanolic extract from dried leaves (IC50=1.02 mg/mL) showed higher antioxidant activity than the fresh leaves (IC50=1.34 mg/mL). In addition, the extract from dried leaves also exhibited the higher tyrosinase inhibitory activity when compared with the activity of extract from fresh leaves with IC50 value of 0.064 ppt but lower than standard vitamin C (IC50 =0.045 ppt). Conclusions: This study showed that the dried leaves of Seablite could be further studied about pharmacological product to apply in the cosmetic industry and to increase the economic values of Thai medicinal plants Keywords: Suaeda Maritime L. Antioxidant Activity Tyrosinase Inhibition Activity